Neo Sufisme: Sebuah Gerakan Pembaharuan Moral - Firdausi, M. Anwar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2004)
Really Neo Sufism noted new term in the Islamic studies because this term is as the continuation of the Islamic studies it self (Sufism) that is always based on the Qur'an and Hadits. One of Â Neo Sufism movements that took place in North Africa is as a mode of the Islamic studies movement that tries to think over the Sufism thought in syariat environment that that is very active in undergoing moral revival that often appears in politic activities.